2021
DOI: 10.3390/ijms22136843
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gut Bacterial Communities of Grapholita molesta (Lepidoptera: Tortricidae) Reared on Different Host Plants

Abstract: Intestinal symbiotic bacteria have played an important role in the digestion, immunity detoxification, mating, and reproduction of insects during long-term coevolution. The oriental fruit moth, Grapholita molesta, is an important fruit tree pest worldwide. However, the composition of the G. molesta microbial community, especially of the gut microbiome, remains unclear. To explore the differences of gut microbiota of G. molesta when reared on different host plants, we determined the gut bacterial structure when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 63 publications
4
30
0
Order By: Relevance
“…They mainly included sugar synthesis and metabolism, carbohydrate transport and metabolism, amino acid transport and metabolism, nervous system and immunity, etc. This conclusion is similar to those of studies of G. molesta [18,47,48], which analyzed the significant differences in predicted function between different hosts, and concluded that feeding on different hosts can cause differences in metabolism and resistance to drugs and cancer. Previous studies have shown that the gut microbiota of the FAW can change the metabolic process of insecticides and improve detoxification efficiency under the pressure of pesticide selection [17].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…They mainly included sugar synthesis and metabolism, carbohydrate transport and metabolism, amino acid transport and metabolism, nervous system and immunity, etc. This conclusion is similar to those of studies of G. molesta [18,47,48], which analyzed the significant differences in predicted function between different hosts, and concluded that feeding on different hosts can cause differences in metabolism and resistance to drugs and cancer. Previous studies have shown that the gut microbiota of the FAW can change the metabolic process of insecticides and improve detoxification efficiency under the pressure of pesticide selection [17].…”
Section: Discussionsupporting
confidence: 87%
“…In recent years, more insect microbial communities have been discovered and studied. Studies have been reported in honeybees [34][35][36][37], fruit flies [38][39][40], mosquitoes [41,42], Dectes texanus [43], and termites [44,45], as well as in lepidopteran pests, such as Grapholita molesta [18,[46][47][48], Carposina sasakii [46,47], and Cydia pomonella [47]. The gut microbial community of the honeybee has stable species and structure, and there are many unique microbial types in different regions of Apis mellifera.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diet is one of the important factors for insect development ( Karley et al, 2002 ; QubaiovĂĄ et al, 2021 ), and it also plays an important role in shaping insect phenotypes and gut microbial communities ( Colman et al, 2012 ; Xu et al, 2019 ; Luo et al, 2021 ; Mason et al, 2021 ). Host diet could influence the diversity, structure, or composition of the gut in many insects ( Strano et al, 2018 ; LĂŒ et al, 2019 ; Leite-Mondin et al, 2021 ; Yuan et al, 2021 ). Leite-Mondin et al (2021) discovered that the gut microbiota composition of Trichoplusia ni (Hubner) altered by diet may influence its polyphagous behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear how the living environment of grasshoppers affect their gut microbes. Yuan et al confirmed that the gut bacterial structure of G. molestacan be influenced by the host plant [ 32 ]. Moro et al showed that the diversity of gut microbes of the same species in regions was different [ 33 ].…”
Section: Discussionmentioning
confidence: 99%